2013
DOI: 10.2967/jnumed.112.113639
|View full text |Cite
|
Sign up to set email alerts
|

V/Q SPECT Interpretation for Pulmonary Embolism Diagnosis: Which Criteria to Use?

Abstract: Ventilation-perfusion (V/Q) SPECT has been reported to improve the diagnostic performance of V/Q imaging for the diagnosis of pulmonary embolism (PE). However, only sparse data based on an objective reference test are available, and the criteria used for interpretation have varied widely. Therefore, the aim of our study was to assess the performance of V/Q SPECT using various criteria for interpretation, in comparison with a validated independent diagnostic strategy. Methods: The SPECT study included patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 18 publications
0
39
0
5
Order By: Relevance
“…V/Q SPECT was interpreted by the nuclear medicine physician in charge using a diagnostic cutoff of one segmental or two subsegmental mismatched defects [16]. The final diagnostic conclusion was established by the physician in charge of patient care on the basis of clinical symptoms, laboratory tests, V/Q SPECT and other imaging procedures performed.…”
Section: Initial V/q Spect Interpretation Diagnostic Management and mentioning
confidence: 99%
See 1 more Smart Citation
“…V/Q SPECT was interpreted by the nuclear medicine physician in charge using a diagnostic cutoff of one segmental or two subsegmental mismatched defects [16]. The final diagnostic conclusion was established by the physician in charge of patient care on the basis of clinical symptoms, laboratory tests, V/Q SPECT and other imaging procedures performed.…”
Section: Initial V/q Spect Interpretation Diagnostic Management and mentioning
confidence: 99%
“…Compared with traditional planar V/Q imaging, V/Q SPECT offers a better spatial resolution and a limitation of the overlapping of perfusion defects by other structures [8][9][10]. The diagnostic performance of V/Q SPECT has been reported in several accuracy and cohort studies [11][12][13][14][15], and interpretation criteria dedicated to V/Q SPECT have been validated [16][17][18]. Improved performance of V/Q SPECT could allow safe and simplified algorithm strategies while maintaining the advantages of V/Q scintigraphy (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…For V/Q SPECT, the most commonly used criteria (60%) were those proposed by the EANM, that is, a binary approach (PE or no PE) with a diagnostic cutoff of "1 segmental or 2 subsegmental perfusion mismatched defects" (18). This diagnostic cutoff has been reported to be optimal for PE diagnosis (36), and a recent observational study confirmed the diagnostic exclusion safety of a diagnostic management including a V/Q SPECT study interpreted with these criteria (37). Only 8% of institutions used the probabilistic approach for interpretation of SPECT, compared with 29% for planar.…”
Section: Discussionmentioning
confidence: 66%
“…The agents used for V SPECT differed (Table 1) and the diagnostic criteria for interpretation of SPECT also differed among investigations (Table 1). Le Roux et al [39], in a subset of patients reported by Le Duc-Pennec et al [26], showed the best performance of SPECT with a diagnostic cutoff of C1 segmental or C2 subsegmental mismatches [sensitivity: 45 out of 49 (92 %), specificity: 182 out of 200 (91 %)].…”
Section: Non-diagnosticmentioning
confidence: 97%